Case report: Double filtration plasmapheresis (DFPP) for severe rhesus-D alloimmunization in two pregnant patients - Liang, Yuling; Wang, Tenghui; Zhu, Wenjian; Wang, Xiaohua; Zhang, Xuemei; Zheng, Zhihua; Lei, Yan (Frontiers in Pediatrics, 2023)
Erythrocyte alloimmunization is one of the most important causes of fetal anemia. The standard treatment for anemic fetuses is intrauterine blood transfusion (IUT). However, IUT may have adverse effects especially before 20 weeks of gestation. In this report, two women who have had previously severely affected alloimmunised pregnancy developed high titers of anti-D antibodies before 20 weeks of gestation. Ultrasound Doppler showed severe fetal anemia, and intrauterine transfusion was expected to be unavoidable. To prolong pregnancy to a gestation where intravascular IUT is possible, we used repeated double filtration plasmapheresis (DFPP) as a rescue therapy. The titers of IgG-D, as well as that of IgG-A and IgG-B decreased tremendously after DFPP treatment. One woman successfully prolonged pregnancy until 20 weeks of gestation. Then she underwent 4 cycles of IUTs and delivered at 30 weeks of gestation by emergency caesarean section due to fetal bradycardia during the 5th intrauterine transfusion. The other woman successfully delayed intrauterine transfusion until 26 weeks of gestation. The favorable results of the two patients indicate that DFPP is an effective and safe treatment modality for the treatment of RhD immunity in pregnant women, especially for those complicated with maternal ABO incompatible hemolytic anemia. However, more clinical trials are further needed to verify the results.